Clinical and Epidemiological Aspects of Monkeypox: An Emerging Zoonosis with Worldwide Distribution - Samadi, Assadullah (Journal of Natural Sciences – Kabul University, 2023)
Monkeypox is an emerging viral zoonotic disease that has recently spread worldwide. Wild animals, particularly various species of monkeys and small rodents, serve as primary reservoirs for the virus. Humans become infected mainly through contact with infected animals or exposure to infected individuals. Although smallpox was eradicated in 1977, the emergence of monkeypox infections in human populations and its rapid global spread in 2022 have raised significant concerns about the potential recurrence of smallpox-like events, historically associated with high human casualties. In response, the World Health Organization has declared monkeypox a public health emergency of international concern, necessitating immediate and coordinated global measures.